2012
DOI: 10.1371/journal.pone.0047045
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Macrophages with a M1 or M2 Phenotype in Relation to Prognosis and the Molecular Characteristics of Colorectal Cancer

Abstract: High macrophage infiltration has been correlated to improved survival in colorectal cancer (CRC). Tumor associated macrophages (TAMs) play complex roles in tumorigenesis since they are believed to hold both tumor preventing (M1 macrophages) and tumor promoting (M2 macrophages) activities. Here we have applied an immunohistochemical approach to determine the degree of infiltrating macrophages with a M1 or M2 phenotype in clinical specimens of CRC in relation to prognosis, both in CRC in general but also in subg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
403
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 421 publications
(424 citation statements)
references
References 58 publications
18
403
1
2
Order By: Relevance
“…M2 macrophages are generally considered to be involved in tissue repair and wound healing processes and produce the cytokines IL-10 and TGF-b. Markers of M2 differentiation include arginase-1 and the surface marker CD163 [76][77][78][79][80].…”
Section: Iav Replication and Macrophage Phagocytosismentioning
confidence: 99%
“…M2 macrophages are generally considered to be involved in tissue repair and wound healing processes and produce the cytokines IL-10 and TGF-b. Markers of M2 differentiation include arginase-1 and the surface marker CD163 [76][77][78][79][80].…”
Section: Iav Replication and Macrophage Phagocytosismentioning
confidence: 99%
“…In general, tumor-associated macrophages can be found within or surrounding various tumors, where they either promote tumor progression, angiogenesis, migration of tumor cells and T helper 2 responses (so-called M2 or alternative macrophages), or, conversely, they promote resistance to tumors, inflammatory responses and T helper 1 responses (so-called M1 or classical macrophages). 15,16 Although macrophages have been found in colorectal tumor sections, 17,18 the correlation of their abundance with the prognosis of MSI neoplasms is not yet clear.…”
Section: Introductionmentioning
confidence: 99%
“…TAMs have been shown to be highly plastic cells that can display both tumor preventing (M1 macrophages) and tumor promoting functions (M2 macrophages) (9,10). further studied on the distribution of M1 and M2 macrophage phenotypes in colorectal cancers showed that patients who had high numbers of infiltrating M1 macrophages obtained a significantly better prognosis (11). M1 macrophages stimulated cell-mediated responses via secreting pro-inflammatory cytokines such as IL-1, IL-6, IL-12, IL-23 and TNf-α.…”
Section: Introductionmentioning
confidence: 99%